Integrating multi-level interactive network analysis and in vivo studies to explore the protective mechanism of Maillard products of skipjack trypsin hydrolysate in hyperuricemia - Xueping Wang; Jiaxing Wang; Yurou Chu; Jipeng Sun; Ru Song; Bin Zhang (Journal of Functional Foods)
This study used skipjack by-products to produce skipjack trypsin hydrolysate (STH), which was then processed through the Maillard reaction to create its Maillard product, STHMS3 (200–1000 Da). We evaluated STHMS3's protective effects against hyperuricemia-induced renal injury in mice. Utilizing in vivo experiments, network pharmacology, and molecular docking, we explored its protective mechanisms. STHMS3 significantly decreased serum uric acid, creatinine, blood urea nitrogen, and xanthine oxidase (XOD) levels, reduced oxidative stress, and enhanced antioxidant protein levels in kidneys. Network pharmacology analysis showed STHMS3's interaction with multiple targets and pathways, including apoptosis, NF-κB, and TNF signaling pathways, suggesting a multi-level interactive network mechanism. Molecular docking confirmed STHMS3's ability to directly inhibit XOD through hydrogen bond formation. This study highlights the therapeutic potential of food-derived peptides in managing hyperuricemia and protecting renal function.